Policy Incentives, Competitive Landscape, and Potential Evaluation:: A Multidimensional Study on Chinese New Energy Vehicles in the Malaysian Market - Liyan Cao; Mohd Farid Shamsudin (Asia Pacific Journal of Social Science Research, 2025)
The global automotive industry is undergoing a profound transformation towards electrification, with Chinese New Energy Vehicle (NEV) manufacturers emerging as pivotal players on the international stage. Malaysia, as a strategic automotive hub in Southeast Asia, presents a burgeoning and highly competitive market for NEVs. This study conducts a comprehensive multidimensional analysis of the penetration and development strategies of Chinese NEVs within the Malaysian market. The research is structured around three core dimensions: policy incentives, the competitive landscape, and market potential evaluation. Firstly, the paper dissects the intricate web of national and state-level policy incentives in Malaysia, including tax exemptions, import duty structures, and initiatives like the National Automotive Policy (NAP) 2020 and the Low Carbon Mobility Blueprint (LCMB) 2021-2030. It evaluates how these policies create both opportunities and barriers for Chinese brands. Secondly, it maps the competitive landscape, contrasting the aggressive strategies of Chinese OEMs (e.g., BYD, Great Wall Motor, Chery) with established Japanese incumbents (e.g., Toyota, Honda), nascent local EV players (e.g., Proton, smart 1 under Proton-NB), and other international brands. The analysis employs frameworks like Porter’s Five Forces to understand the dynamics of this evolving sector. Thirdly, the study employs a PESTEL analysis and quantitative market forecasting models to evaluate the future growth potential, identifying key drivers such as rising environmental consciousness, economic development, and government targets, alongside significant challenges including consumer range anxiety, underdeveloped charging infrastructure, and economic volatility. The conclusion synthesizes these findings to propose strategic recommendations for Chinese NEV manufacturers to navigate the complexities of the Malaysian market, for Malaysian policymakers to optimize their regulatory framework, and for future academic research. This study contributes to the literature on international business expansion of emerging market multinationals and the geopolitics of technology in the global EV supply chain.